Special Issue on Advanced Technologies in Seismic Design, Assessment and Retrofitting - Konstantinos Morfidis; Konstantinos Kostinakis (Applied Sciences)
The seismic design of new structures, as well as the assessment of seismic vulnerability and the retrofitting or rehabilitation of existing structures, are two important research fields in civil engineering [...]